Physico-chemical and electrical properties of bismuth chromate solid solutions - Wong, Y. C.; Tan, Yen Ping (Universiti Putra Malaysia Press, 2013)

(untitled)
Bismuth chromium solid solutions, with a general formula Bi6-xCr2Oδ, where -1 ≤ x ≤ 2, were successfully synthesized via the conventional solid state method. The phases of the synthesized samples were determined by X-ray diffraction (XRD) analysis. The properties of single-phase compounds were characterized by using differential thermal analysis (DTA), thermal gravimetric analysis (TGA), AC impedance spectroscopy, and inductively coupled plasma-atomic emission spectroscopy (ICP-AES). The occurrence of phase transitions was confirmed by DTA and TGA, where a thermal event was observed by DTA at around 800°C. In addition, TGA studies also showed that there was a weight loss at around 800°C. Elemental analysis of Bi6Cr2O15and its solid solutions by ICP-AES showed a good agreement between the expected value and the experimental value on the compositions, with no evidence of any systematic deviation from stoichiometric. Electrical properties of Bi6Cr2O15and its solid solutions were investigated by using AC impedance spectroscopy from 300°C to 650°C. Ionic conductivity increased with the increasing temperature and bismuth content, and the best ionic conductivity was observed for Bi7Cr2O16.5. The activation energy (Ea) of Bi6Cr2O15and its solid solutions were in the range of 1.22-1.32 eV.